AgNPs Incorporated in PMMA-PVP blended nanofibers: spectroscopy monitoring of AgNP dissolution in PMMA nanopores - Plokhotnichenko, Alexander; Karachevtsev, Victor (Biophysical Bulletin, 2025)
Background: Electrospun polymeric nanofibers incorporated with some biologically active nanoparticles have a huge range of various applications in biomedical fields. Blending several polymers with different properties allows one to obtain a new material with improved characteristics, as well as to control the incorporation and release of medical agents.Objectives: To elaborate an approach for the preparation of biocompatible nanofibers using a blend of two polymers (polyvinylpyrrolidone (PVP) and polymethyl methacrylate (PMMA)) with incorporated silver nanoparticles (AgNPs) and to apply the absorption spectroscopy for determining of the average nanoparticle diameter and monitoring of AgNP dissolution from PMMA nanopores.Materials and methods: A blend of hydrophilic (PVP) and water-insoluble (PMMA) polymers is proposed for nanofiber preparation with incorporated AgNPs. The absorption peak position of the band due to localized surface plasmon resonance (LSPR) and its intensity in the UV-vis spectrum were used to characterize AgNPs and to estimate the influence of the environment.Results: A new method for fabricating nanofibers from a mixture of two polymers, one water-soluble (PVP) and the other soluble only in organic solvents (PMMA), with AgNPs, has been developed. The diameter of the nanofibers is determined to be in the range of 2-4 μm. The average nanoparticle diameter determined by the position of the absorption peak due to LSPR in the UV-vis spectrum is 35-40 nm. The peak shift of this band in different environments was determined in comparison with the spectrum obtained in an aqueous solution. A decrease in the intensity of the band was observed with an increase in the mat incubation time in the oxidizing solution, and a blue shift of the band maximum was detected, which indicates a decrease in the average size of AgNPs during their dissolution.Conclusions: In the blended nanofibers, PVP environment of AgNPs facilitates their incorporation into PMMA and provides access of water molecules to nanoparticles, while PMMA provides the mechanical strength of the nanofibers. The appearance of AgNPs from the polymeric nanofibers soaked in water was not detected, since they are fixed in the structure of the water-insoluble polymer. Nevertheless, the experiments with the mat soaking in the oxidative solution showed that the nanopores in PMMA incorporated with AgNPs are open. This observation indicates the possibility of a gradual release of Ag+ ions from such nanofibers.